Contributions of Acharya Dalhana in Susrutha Samhita (AYUSHDHARA, 2024)
Susrutha Samhita is the representative treatise of the Indian school of surgery (Shalyatantra) popularly known as “Dhanwantara sampradaya”. Susruta Samhita mainly has significantly developed different Surgical techniques, Even, in which Acharya Susruta beautifully elaborated and has all shades of his opinion as throwing light upon general principles, diagnosis, Anatomy, pathology, prognosis, pharmacology, toxicology, surgical procedures like Sandhana Karma, cosmetic surgery and etc. the commentaries are always useful in easier understanding of the Samhita with its deep and hidden contents properly. There are many commentaries available for Susrutha Samhita but the commentary Nibandha Sangaraha written by Acharya Dalhana is the only available commentary in its entirely. Dalhana’s commentary is important in the sense that it explains the ideas clearly with requisite elaboration which are not mentioned explicitly in the text. This article is aimed to highlight the contributions of Dalhana in his commentary of Susrutha Samhita.